Extracorporeal Ureteric Stenting for Pediatric Laparoscopic Pyeloplasty - Kocherov, Stanislav; Lev, Genady; Chertin, Leonid; Chertin, Boris (European Journal of Pediatric Surgery, 2016)
Introduction We aimed to evaluate a novel technique for ureteric stent insertion during dismembered pediatric laparoscopic pyeloplasty.Patients and Methods Following identification and dissection of the ureteropelvic junction (UPJ) with the proximal part of ureter, the ureter is dismembered just proximal to the UPJ at the level of the renal pelvis, allowing use of the excess pelvic tissue for further manipulation of the ureter. Then the abdomen is desufflated and the ureter delivered to the skin level. The externalized ureter is then spatulated and the stent inserted in an antegrade fashion to the bladder. The first stitch for further laparoscopic anastomosis is applied to the lower part of the spatulated ureteric end and then following insufflations the ureter is returned to the abdomen. The laparoscopic anastomosis is completed in a routine fashion.Results Over the past 4 years, we have used this technique in 26 children (17 boys and 9 girls) with median age of 4 years (range, 2–18 years). Left pyeloplasty was performed in 16 and right pyeloplasty in the remaining 10 patients. The mean (range) time of insertion was 6 minutes (range, 4–7 minutes). All stents were correctly placed. In one patient, the stent dislodged to distal part of the ureter. No other intraoperative or postoperative complications related to our technique of stent insertion were observed.Conclusion Our data show that extracorporeal antegrade ureteric stent insertion is an easy-to-learn and a safe and reliable technique for pediatric dismembered pyeloplasty. It obviates the problem of having the stent in the pelvis during dissection and the need for patient repositioning.
Keywords: extracorporeal stenting; laparoscopic pyeloplasty; pediatric